Cost Benefit Analysis dalam Pengembangan Fasilitas Pengolahan Sampah: Studi Kasus Kota Pekanbaru - Mochammad Chaerul; Silda Adi Rahayu (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Municipal solid waste management is a public service that should be provided by the government and needs a significant portion of the government budget, so it is deemed as a cost center. Often, benefit from the waste management could not directly be nominalized into money. The study aims to compare the total cost needed and benefit taken, directly and indirectly, using Cost Benefit Analysis (CBA) and puts Pekanbaru City as a case study. Recently, there were 5 units of waste recycling facility (TPS 3R), 5 units of composting facility, and 145 unit of waste bank available in Pekanbaru City. In order to compare with the existing condition, the study developed 2 scenarios related to the recycling facilities, namely Scenario A for optimizing capacity of the facilities, and Scenario B for providing 2 facilities in each sub-district until 2025. The result shows that the Benefit Cost Ratio (BCR) value were 2.903 for Scenario A, and 4.478 for Scenario B, comparing to 1.624 for the existing condition. The study provides a proof that the municpality should prioritze waste treatment rather than waste disposal as it has higher total benefit and the measure is in-line with the national policy on waste management.